RECENT ADVANCES IN GAS, LIQUID AND SUPERCRITICAL FLUID CHROMATOGRAPHY IN THE CONTEXT OF SUSTAINABLE/ GREEN CHEMISTRY - Nimra Sohail; Bushra Naureen; Mehmood Asghar; Aziza Sarwar; Aisha Altaf (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Background: Chromatographic techniques such as gas chromatography (GC), liquid chromatography (LC) and supercritical fluid chromatography (SFC) have long been employed in analytical chemistry. However, using or producing certain organic solvents and non-renewable gases is hazardous to the environment. Green chemistry is essential for addressing the environmental hazards associated with traditional procedures. Objectives: This review focuses on recent updates and profound insights into new, greener techniques introduced in GC, LC and SFC. Methodology: To compile this review, several electronic databases were searched, preferably from January 2019-December 2023. Results: This review highlights advancements in miniaturization, rapid methods, and eco-friendly solvents in chromatographic techniques. Integrating micro-electro-mechanical systems (MEMS) and nano-electro-mechanical systems (NEMS) in GC enhances sensitivity and resolution while reducing solvent consumption. Innovations like monolithic micro-GC chips and the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method further streamline analysis times. In LC, supercritical fluids are utilized as green mobile phases, optimizing techniques like electrochemical flow liquid chromatography (EFLC), high-performance liquid chromatography (HPLC), and ultra-high-performance liquid chromatography UHPLC. In contrast, SFC employs rapid methods, such as ultra-high-performance supercritical fluid chromatography-mass spectrometry (UHPSFC-MS). These developments collectively promote sustainability and efficiency in chromatographic practices. Conclusion: Green chromatography has become an essential tool in pharmaceutical analysis because it safeguards the operator’s health and the environment. It opens new horizons and generates new ideas for further experimentation while focusing on recent cutting-edge green technologies incorporated in GC, LC and SFC. These advancements significantly enhance safety and sustainability in analytical practices.